GAMBARAN KEPRIBADIAN GELAP (DARK TRIAD PERSONALITY) PADA PENGGUNA MEDIA SOSIAL - Rizal, Irfani; Handayani, Benni (UIR Press, 2021)
Nowadays, humans today are inseparable from the sophistication of information and communication technology, all people can enjoy the sophistication of today's technology, be it children, adolescents, adults, and even parents who cannot be separated from technology. In Indonesia, the age range is from 15 years to 24 years and is the largest user. The sampling technique used in this study was purposive sampling. The research subjects were 386 respondents and were active social media users. The measuring instrument used in this study uses an adaptation scale of dark triad personality by Jones and Pauhlus (2014) which consists of 26 items that the authors translate and adapt to the Indonesian culture. The purpose of this study was to describe the dark triad of personality among social media users. A dark personality is a personality that is dominated by negative behavior. The results showed 15.80% had high traits of Machiavellianism, 14.76% had high traits of narcissism, and 15.02% had high traits of psychopathy. Based on the results of the analysis of the mean value of personality factors based on the dark triad personality theory, it can be concluded that in general, the highest mean value is on the trait of Machiavellianism with a mean value of 21.09 and the lowest score lies in the characteristics of psychopathy, namely 11.20. Most social media users are Instagram with a percentage of 95.5% then Instant Massaging (Wa / Line) at 83.8% and Facebook at 53%. The dark personality or dark triad personality is a personality that is dominated by negative behavior so that in the Islamic perspective it is included in the personality of anger, which means that the individual tends to the character of the body and teaches the principle of enjoyment.